Development Of Science Learning Devices For Junior High School On Light And Optical Tools Oriented Towards Integrated Process Skills Character Education - Vioni, Herti (Gravity Journal, 2025)
The materials development was conducted due to fact which indicated the limited learning materials in IPA subject in accordance with the students’ needs and scientific thoughts. Besides, the existing learning materials had not been able to foster students’ positive character values. This study was aimed at developing learning tools through Process Skills Approach which was integrated with Characters Building that is valid, practical, effective and worthy to be used in learning process. Thus, it was assumed that those learning tools could improved students' learning outcomes and positive character. This was a developmental research (research and development). The development model used was 4-D model which consisted of defining level (define), planning (design), developing (development) and disseminating (disseminate). In defining level, the curriculum, students and materials were analyzed inplanning level, the learning tools such as syllaby, lesson plan, handout, student’s worksheet, assessment of cognitive, affective, character psychomotor, project, and performance were designed. In developing level, the validity was tested through learning tools validation sheets. The practicality test was lested through lesson plan observation sheet, teachers’ and student’s response questionnaire, and the effectivity was tested through cognitives, affective, characters, psychomotor, project, and performance assesment with student’s responses questionnaire. This research produced IPA learning tools for junior high school on light and optical instrument by using Process Skills approach orientation integrated with character building that was very valid, practical and effective.